Examination of the Anxiety of Catching the Novel Coronavirus (COVID-19) in Elite Athletes and Sedentaries: Examination of the Anxiety of Catching the Novel Coronavirus (COVID-19) in Elite Athletes and Sedentaries - TEKKURŞUN DEMİR, Gönül; BULĞAY, Celal; ÇAKIR, Ozan Veli; BAYRAKTAR, Işık; ÇETİN, Ebru (IJERI: International Journal of Educational Research and Innovation, 2020)
The present study aims to examine the anxiety to catch COVID-19 from the viewpoint of elite athletes and sedentaries based on different variables. The Individual Anxiety sub-dimension of the Athlete’s Anxiety to Catch the Novel Coronavirus (COVID-19) Scale was applied. According to the study results, athletes had lower levels of anxiety to catch COVID-19 compared to sedentaries. It was concluded that female participants had higher levels of anxiety compared to male participants. It was also determined that female elite athletes also had higher levels of anxiety compared to male elite athletes. When the anxiety to catch COVID-19 was examined by age group, it was observed that elite athletes under the age of 19 had significantly lower levels of individual anxiety compared to other age groups. Additionally, it was found that male elite athletes had lower levels of anxiety compared to male sedentaries.